Frequency-Varying Spectral Shear Interferometry for Characterization of Extremely Short Attosecond Pulses - Jiangfeng Zhu; Shaobo Fang; Yamane, Keisaku; Yamashita, Mikio (IEEE journal of quantum electronics, 2011)
We theoretically investigate the complete amplitude and phase characterization of the isolated attosecond extreme ultraviolet (XUV) electric field by the spectral phase interferometry technique. Spectral shear needed for reconstruction of the spectral phase of the XUV pulse is prepared by modulating the driving optical pulse into two with different central wavelengths. We find that the spectral shear between the XUV pulses is almost linearly variable with the frequency, thus the phase reconstruction algorithm is modified by a non-uniformly sampled step concatenation. Numerical simulation using the harmonic spectrum and phase obtained from the saddle point analysis based on the widely used Lewenstein model indicates that this novel method is capable of measuring extremely short attosecond XUV pulses with several advantages owing to the all-optical apparatus: high efficiency and high time resolution, possibility of single-shot measurement, which provides a beneficial improvement to the current complicated photoelectron spectroscopic technique. We suggest that such a method is easy to implement, and propose a feasible experimental arrangement.